Digital Culture and Social Networks of Plant-Based Meat Consumers on Social Media Ethnological Studies in Digital Communities - Kijjaornsathien, Suthida; Munlum, Satitpong; Sriwannawit, Chanika (Dusit Thani College Journal, 2023)
This research is a qualitative research based on digital ethnology with the aim of studying the culture and social networks of consumers of meat substitutes on social media. The results showed that the digital culture of consumers of meat substitutes on social media has two issues: 1) Health. Consumers have a positive attitude towards plant-based meat substitutes because plant-based foods are of good quality, high nutritional value. Equivalent The consumption of plant-based meat products can reduce the destruction of the natural environment because animal husbandry causes carbon dioxide from the meat farming process and produces greenhouse gases that cause global warming. However, the consumption of plant-based meat does not cause environmental damage. In addition, a study of social networks of meat substitutes consumers on social media also found that consumers have created networks to communicate with groups who prefer to consume plant-based meat on knowledge sharing, health, and most of them focus on Interested in the same subject, network groups also follow the fan pages of groups that are socially connected or in their interests to exchange news on the consumption of plant-based meat.